Fishes in a changing world: learning from the past to promote sustainability of fish populations - T. A. C. Gordon; H. R. Harding; F. K. Clever; I. K. Davidson; W. Davison; D. W. Montgomery; R. C. Weatherhead; F. M. Windsor; J. D. Armstrong; A. Bardonnet; E. Bergman; J. R. Britton; et al. (Journal of Fish Biology, 2018)
Populations of fishes provide valuable services for billions of people, but face diverse and interacting threats that jeopardize their sustainability. Human population growth and intensifying resource use for food, water, energy and goods are compromising fish populations through a variety of mechanisms, including overfishing, habitat degradation and declines in water quality. The important challenges raised by these issues have been recognized and have led to considerable advances over past decades in managing and mitigating threats to fishes worldwide. In this review, we identify the major threats faced by fish populations alongside recent advances that are helping to address these issues. There are very significant efforts worldwide directed towards ensuring a sustainable future for the world's fishes and fisheries and those who rely on them. Although considerable challenges remain, by drawing attention to successful mitigation of threats to fish and fisheries we hope to provide the encouragement and direction that will allow these challenges to be overcome in the future.

Directional gene flow patterns in disjunct populations of the black ratsnake (Pantheropis obsoletus) and the Blanding’s turtle (Emydoidea blandingii) - Briar J. Howes; Joseph W. Brown; H. Lisle Gibbs; Tom B. Herman; Stephen W. Mockford; Kent A. Prior; Patrick J. Weatherhead (Conservation Genetics, 2009)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)